Effectiveness of 222-nm ultraviolet light on disinfecting SARS-CoV-2 surface contamination - Kitagawa, Hiroki; Nomura, Toshihito; Nazmul, Tanuza; Omori, Keitaro; Shigemoto, Norifumi; Sakaguchi, Takemasa; Ohge, Hiroki (American journal of infection control, 2021)
•222-nm UVC light (0.1 mW/cm2) reduced viable SARS-CoV-2 by 0.94 log10 in 10 seconds.•222-nm UVC light (0.1 mW/cm2) reduced viable SARS-CoV-2 by 2.51 log10 in 30 seconds.•222-nm UVC light did not reduce SARS-CoV-2 RNA copy number after 5-minute irradiation.•TSID50 and not RT-qPCR should be used to monitor far-UVC disinfection of surfaces. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes coronavirus disease 2019 (COVID-19), has emerged as a serious threat to human health worldwide. Efficient disinfection of surfaces contaminated with SARS-CoV-2 may help prevent its spread. This study aimed to investigate the in vitro efficacy of 222-nm far-ultraviolet light (UVC) on the disinfection of SARS-CoV-2 surface contamination. We investigated the titer of SARS-CoV-2 after UV irradiation (0.1 mW/cm2) at 222 nm for 10-300 seconds using the 50% tissue culture infectious dose (TCID50). In addition, we used quantitative reverse transcription polymerase chain reaction to quantify SARS-CoV-2 RNA under the same conditions. One and 3 mJ/cm2 of 222-nm UVC irradiation (0.1 mW/cm2 for 10 and 30 seconds) resulted in 88.5 and 99.7% reduction of viable SARS-CoV-2 based on the TCID50 assay, respectively. In contrast, the copy number of SARS-CoV-2 RNA did not change after UVC irradiation even after a 5-minute irradiation. This study shows the efficacy of 222-nm UVC irradiation against SARS-CoV-2 contamination in an in vitro experiment. Further evaluation of the safety and efficacy of 222-nm UVC irradiation in reducing the contamination of real-world surfaces and the potential transmission of SARS-CoV-2 is needed.